Disaster Response in Indonesia: Initiating Income Tax Policy Pro Disaster Mitigation - Dini Dubelmar; Made Astrin Dwi Kartini; Sabila Mareli; Murwendah Murwendah (Politik Indonesia: Indonesian Political Science Review)
As a country with high potential for natural disaster, Indonesia can suffer from economic disruptions arising from significant decline in gross domestic income (GDP) due to financing losses caused by natural disaster. To reduce the risk of loss caused by natural disasters, the government has issued disaster mitigation policies in the form of structural and non-structural policies. In 2018, the government initiated a disaster mitigation policy in the form of natural disaster insurance prioritized to protect state assets. It does not exclude the possibility that this insurance shall be given to civil society, yet an issue arises regarding the source of funding for the insurance. Tax instruments are expected to be a policy innovation to overcome the issue of financing insurance. The purpose of this study is to explore the potential and role of fiscal policy through tax instruments in the context of disaster management in Indonesia. This study applied a qualitative approach and collected data through field studies and in-depth interviews. The findings of this study indicate that the natural disaster insurance policy may adopt the concept of tax allowance on donation and zakat as stipulated in Law No. 36 of 2008 on Income Tax. This incentive provides a tax facility in the form of tax allowance on income for calculating Income Tax. The policy is expected to attract the community to participate in natural disaster insurance amid the general lack of participation in insurance in Indonesia. On the other hand, the government obtains a source of revenue to finance disaster mitigation without disrupting the economy of the country.